Numerical modeling and experimental investigation of the flow and thermal processes in a motor car vehicle underhood - Van Zyl, Josebus Maree (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2006.